Online Monitoring Method for Capacitor Lifetime in Brushless DC Motor Drive Systems with DC-Link Series Switch - Zhongquan Qian; Siyang Gong; Shuxin Xiao; Zhichen Lin; Xinmin Li (World Electric Vehicle Journal, 2025)
Brushless DC motors are often used as traction motors in electric vehicles due to their high power density and efficiency. The dc-link electrolytic capacitor is the most vulnerable part of the brushless DC motor drive system, and it determines the reliability of the motor drive system. Therefore, it is of great importance to monitor the life of the dc-link electrolytic capacitor in the drive system. To carry out the lifetime monitoring of capacitors, a dc-link series switch circuit composed of diodes and power switching devices is introduced to calculate the capacitance value. The lifetime of the capacitor is then monitored in real time through this capacitance value. During normal steady-state operation of the motor, the control strategy of the inverter is switched. When the dc-link switch is turned off, the charging vector is used to charge the dc-link capacitor. Due to the presence of the diode and the dc-link switch, the energy charged to the dc-link by the motor can only flow into the capacitor and cannot be released immediately. Therefore, the capacitance value is calculated through the change in capacitor voltage and the capacitor current reconstructed from the three-phase currents of the motor. The feasibility of the method proposed in this paper is experimentally verified by building a brushless DC motor system.